Heavy Fermion Superconductivity in Non-magnetic Cage Compound PrV2Al20. (January 2016) - Matsumoto, Yosuke; Tsujimoto, Masaki; Tomita, Takahiro; Sakai, Akito; Nakatsuji, Satoru
Abstract: PrT2 Al20 (T = Ti, V) are ideal systems to study the quadrupole Kondo effect and quantum criticality arising from orbital degrees of freedom. Both systems have the nonmagnetic cubic Γ3 crystal electric field ground doublet with the well separated excited state. In particular, PrV2 Al20 exhibits anomalous metallic behavior above and below the multipolar ordering temperatures, reflecting the even stronger hybridization between f and conduction electrons possibly due to a proximity to a orbital quantum critical point. Here, we discuss the heavy fermion superconductivity (SC) of PrV2 Al20 in detail. The SC appears at Tc = 0.05 K with the highly enhanced effective mass (m* /m0 ∼ 140) estimated using the temperature dependence of the upper critical field. In addition, large electronic specific heat coefficient of γ ∼ 0.9 J/mol K 2 above Tc and the large specific heat jump at Tc of ΔC/Tc ∼ 0.3 J/mol K 2 provide direct evidences of the heavy fermion SC. This observation indicates the first realization of the novel SC arising from the orbital fluctuation of the f electrons at ambient pressure.